The pollution haven hypothesis: A geographic economy model in a comparative study - Natalia Zugravu; Sonia Ben Kheder (Fondazione Eni Enrico Mattei (FEEM), 2008)
Although based on theoretical foundations, the pollution haven hypothesis has never been clearly proven empirically. In this study, we re-examine this hypothesis by a fresh take on both its theoretical and empirical aspects. While applying a geographic economy model on French firm-level data, we confirm the hypothesis for the global sample. Through sensitivity analysis, we validate it for Central and Eastern European countries, emerging and high-income OECD countries, but not for the major part of the Commonwealth of Independent States countries. Finally, we show that the pollution haven hypothesis is confirmed in the strongest manner for emerging economies.
Keywords: F12; F18; Q28; 330; FDI; Environmental Regulation; Economic Geography; Pollution Haven Hypothesis